Seismic locations, geochemical variations, attenuation anomalies, geomorphological structures for the 1983-84 unrest at Campi Flegrei caldera - Luca De Siena; Giovanni Chiodini; Giuseppe Vilardo; Edoardo Del Pezzo; Mario Castellano; Simona Colombelli; Nicola Tisato; Guido Ventura (PANGAEA, 2017)
Despite their importance for eruption forecasting the causes of seismic rupture processes during caldera unrest are still poorly reconstructed from seismic images. Seismic source locations and waveform attenuation analyses of earthquakes in Campi Flegrei area (Southern Italy) during the 1982-1984 unrest have revealed a 4-4.5 km deep NW-SE striking aseismic zone of high attenuation offshore Pozzuoli. The lateral features and principal axis of the attenuation anomaly correspond to the main source of ground uplift during the unrest. The seismic swarms correlate in space and time with fluid injections from a deep hot source, inferred to represent geochemical and temperature variations at Solfatara. These injections struck a high-attenuation 3-4 km deep reservoir of supercritical fluids/foams under Pozzuoli and migrated towards a shallower aseismic deformation source under Solfatara. The reservoir became aseismic for two months just after the main seismic swarm (April 1, 1984) due to a SE-to-NW directed input from the high-attenuation domain, likely a dyke emplacement. The unrest ended after fluids migrated from Pozzuoli to the location of the last caldera eruption (Mt. Nuovo, 1538 AD). The results show that a single source controls the largest monitored seismic, deformation, and geochemical unrest at the caldera.
Supplement to: De Siena, L et al. (2017): Source and dynamics of a volcanic caldera unrest: Campi Flegrei, 1983–84. Scientific Reports, 7(1), https://doi.org/10.1038/s41598-017-08192-7